31-Benzyloxy-5,11,17,23,29-penta-tert-butylcalix[5]arene-32,33,34,35-tetraol - Gargiulli, Claudia (International Union of Crystallography, 2012)
The title compound, C(62)H(76)O(5), known to be one of the most versatile synthetic precursors/intermediates of calix[5]arene derivatives, adopts an approximate C (s)-symmetric cone-in conformation. The aryloxybenzyl ring is tilted in such a way that the p-tert-butyl group fills the macrocycle cavity, while the benzyl group moves away from the cavity axis. In the crystal, this conformational arrangement is secured by intra- and intermolecular O—H⋯O hydrogen bonds forming inversion dimers. Four tert-butyl groups are disordered over two orientations, with occupancy ratios of 0.745 (6):0.255 (6), 0.837 (5):0.163 (5), 0.850 (5):0.150 (5) and 0.845 (8):0.155 (8).